Experimental study of natural circulation instability with void reactivity feedback during startup transients for a BWR-type SMR. (August 2015) - Shi, Shanbin; Wu, Zeyun; Liu, Zhuo; Schlegel, Joshua P.; Brooks, Caleb S.; Eoh, Jaehyuk; Yan, Yikuan; Liu, Yang; Yang, Won Sik; Ishii, Mamoru
Abstract: The natural circulation boiling type SMR can experience flow instability during the startup transients due to the void reactivity feedback. A BWR-type natural circulation test loop has been built to perform the nuclear coupled startup transient tests for Purdue Novel Modular Reactor (NMR). This test loop is installed with different instruments to measure various thermal hydraulic parameters. The testing process can be monitored and controlled through PC with the assistance of LabVIEW procedure. The effects of power ramp rate on the flow instability during the nuclear coupled tests were investigated by controlling the power supply based on the point kinetics model with coolant void reactivity feedback. Two power ramp rates were investigated and the results were compared with those of the thermal hydraulic startup transients without void reactivity feedback. The time trace of power supply, system pressure, natural circulation rate, and void fraction profile are used to determine the flow stability during the transients. The results show that nuclear coupled startup transients also experience flashing instability and density wave oscillations. The power curves calculated from point kinetics model for startup transients show some fluctuations due to void reactivity feedback. However, the void reactivity feedback does not have significant effects on the flow instability during the startup procedure for the NMR. Highlights: Overview of flow instabilities with void reactivity feedback. Implement point kinetics model for the nuclear coupled startup transients. Include fuel dynamics for the electric heater rods in the test facility. Investigate the effect of power ramp rate on the nuclear coupled startup transients.